An Anthology of sacred texts by and about women - Young, Serinity (New York : Crossroad, 1993)
"In 1895 Elizabeth Cady Stanton and her "Revising Committee" produced The Woman's Bible, a commentary on passages in the Bible that "do not exalt or dignify women" and "those also in which women are prominent by exclusion." The women's movement has come a long way in the last hundred years, but so too have our knowledge and appreciation of religions other than Judaism and Christianity." "Serinity Young's Anthology of Sacred Texts by and about Women is the first comprehensive comparative sourcebook on women and religion. It makes available readings by and about women from the primary texts of the world's religions. The religions treated include not only the "big seven," Judaism, Christianity, Islam, Hinduism, Buddhism, Confucianism, and Taoism, but the religions of northern Europe, the Ancient Near East, Greece, and Rome, shamanism and tribal religions, as well as more recent alternative religious movements. Each chapter begins with a brief introduction to the religion in question, providing a historical overview with particular regard to women. Then follow representative texts about women (each with its own introduction) from works that are central to their respective traditions. These texts include creation stories, biographies of founders (in which women often play a prominent role), law codes, folklore and fairy tales, the "texts" of tribal peoples, and works explicitly by women. Folklore and fairy tales have particular importance in this book because they generally reveal the beliefs of the "little tradition," which are often in the hands of women, while the "great tradition" is represented by the male-dominated forms of orthodoxy. The works by women here take many forms from theological treatises to mystical poems to poems mourning the loss of a child or husband to the matter-of-fact statements by tribal women, such as Nisa, expressing the uncertainties of any religious knowing."
"Many of the texts included in this anthology are not only "representative texts about women" but formative texts of the various traditions, texts that have seeped into the language and consciousness of their culture and shaped its view of women. In her introduction the author sketches certain themes that are of central importance for the cross-cultural or comparative study of women in world religion: representations of women as evil, women as role models, wisdom as feminine, women religiosi, dualities, goddesses, sex changes and sex disguises, myths and stories of gender conflict. These themes can help guide the reader as she makes her way through virtual libraries of the world's sacred texts. Reading sacred texts in this way, from the perspective of women, can be a radical activity, an activity that, at its best, subverts male dominance of the text."--BOOK JACKET.
Judaism -- Christianity -- Islam -- Ancient Near East, Greece, and Rome -- Northern European Paganism -- Shamanism and Tribal Religions -- Hinduism -- Buddhism -- Confucianism -- Taoism -- Alternative Religious Movements.
Includes bibliographical references and indexes.
Keywords: Women and religion; Sacred books; Anthologie (Descripteur de forme)